Revolutionizing Education with AI Chatbots: Enhancing Learning and Assessment - Azisi, Azisi (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2025)
This paper explores the use of AI chatbots in education to enhance learning and assessment. The study focuses on the development and adaptation of AI chatbots in the context of classroom teaching and small-scale guided scientific inquiry activities. The research aims to increase meaningful learning opportunities and high-quality interactions between teachers and students by introducing learning topics and methods and providing feedback on expected questions. The study also provides opportunities for students to determine their own research methods so that chatbots can be used effectively in designing scientific inquiry learning in a way that enhances student initiative. The research involved 18 participants, consisting of 11 fifth-grade students and 7 sixth-grade students, with 15 of them being male and 3 being female. The participants were studying science activities in a science talent program for 1 year run by a university. These talented students voluntarily participated in various science activities for 3 hours every two weeks. The paper discusses the benefits of using chatbots in education, such as increasing student engagement and participation, providing personalized learning experiences, and enabling automatic assessment of student responses. Additionally, the paper provides examples of chatbots that have been used in educational contexts, such as language learning, mental health support, and academic advising. In conclusion, the use of AI chatbots in education has the potential to revolutionize the way we teach and learn. By providing personalized learning experiences, increasing student engagement and participation, and enabling automatic assessment of student responses, chatbots can enhance the quality of education and make it more accessible to a wider range of learners. The study suggests that AI chatbots can be used effectively in designing scientific inquiry learning in a way that enhances student initiative. Further research is needed to explore the full potential of AI chatbots in education.